Functional morphology of the cave bear (Ursus spelaeus) mandible: a 3D geometric morphometric analysis - van Heteren, Anneke H.; MacLarnon, Ann; Soligo, Christophe; Rae, Todd C. (Organisms Diversity and Evolution, 2016)
The diet of the fossil cave bears (Ursus spelaeus group) has been debated extensively. Thought traditionally to be herbivorous, more recent studies have proposed more meat in the cave bear diet. To test this, the mandibular morphology of cave bears was analysed using 3D geometric morphometrics and compared to that of extant Ursidae. Landmarks for 3D digitisation of the mandible were chosen to reflect functional morphology relating to the temporalis and masseter muscles. Extant and extinct Pleistocene Ursidae were digitised with a MicroScribe G2. Generalised Procrustes superimposition was performed, and data were allometrically and phylogenetically corrected. Principal component analysis (PCA), two-block partial least squares analysis (2B-PLS), regression analysis and discriminant function analysis were performed. PCA and 2B-PLS differentiate between known dietary niches in extant Ursidae. The lineage of the cave bear runs parallel to that of the panda (Ailuropoda melanoleuca) in morphospace, implying the development of morphological adaptations for eating foliage. A regression of shape onto foliage content in the diet and a discriminant function analysis also indicate that the cave bear diet consisted primarily of foliage.